Enterobacter huaxiensis sp. nov. and Enterobacter chuandaensis sp. nov., recovered from human blood. Issue 3 (7th January 2019) - Wu, Wenjing; Wei, Li; Feng, Yu; Kang, Mei; Zong, Zhiyong
Abstract : Enterobacter strains 090008 T and 090028 T were recovered from the blood of two different patients at West China Hospital, Chengdu, PR China in 2017. Phylogenetic analysis based on the 16S rRNA gene and multi-locus sequence analysis of the rpoB, gyrB, infB and atpD housekeeping genes revealed that the two strains were distinct from any previously known species of the genus Enterobacter . Both average nucleotide identity (ANI) and in silico DNA–DNA hybridization (isDDH) values between strains 090008 T, 090028 T and type strains of all known Enterobacter species were lower than the cut-off (≥95–96 % for ANI and ≥70 % for isDDH) to define a bacterial species. The major cellular fatty acids of strains 090008 T and 090028 T are C16 : 0, C17 : 0 cyclo and C18 : 1 ω7 c, which are similar to other Enterobacter species, and the genomic DNA G+C content was 55.73 and 55.68 mol%, respectively. Strain 090008 T can be differentiated from other Enterobacter species by its ability to ferment sucrose, melibiose andd -arabitol, but with a negative methyl α-d -mannopyranoside reaction. Strain 090028 T can ferment potassium gluconate, but is negative forl -fucose, mdecarboxylase, deaminase aelibiose andd -sorbitol, which distinguishes it from all other Enterobacter species. Genotypic and phenotypic characteristics indicate that strains 090008 T and 090028 T represent two novel species of the genus Enterobacter, for which the names Enterobacter huaxiensis sp. nov. and Enterobacter chuandaensis sp. nov. are proposed, respectively. The type strain of Enterobacter huaxiensis sp. nov. is 090008 T (=GDMCC1.1426 T =CCTCC AB 2018174 T =CNCTC 7648 T ) and the type strain of Enterobacter chuandaensis sp. nov. is 090028 T (=GDMCC1.1427 T =CCTCC AB 2018173 T =CNCTC 7649 T ).